Creative Approaches to Color Mass in the Works of Alisher Navoi - Qutliyeva Mahbuba Bekpulatovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This study explores the role of color mass in the works of Alisher Navoi and its application in creative approaches to literary and visual expression. The research examines how color mass contributes to the formation of artistic imagery, compositional balance, and emotional depth, as well as its significance for aesthetic perception and pedagogical practices. In Navoi’s works, color mass is used not only to convey mood and psychological states but also as a tool for developing visual and artistic competencies. The study highlights theoretical and practical aspects of working with color mass, offering insights for both literary analysis and art education.